Pediatric heart allocation and transplantation in Eurotransplant. (23rd June 2014) - Smits, Jacqueline M.; Thul, Josef; De Pauw, Michel; Delmo Walter, Eva; Strelniece, Agita; Green, Dave; de Vries, Erwin; Rahmel, Axel; Bauer, Juergen; Laufer, Guenther; Hetzer, Roland; Reichenspurner, Hermann; et al.
Summary Pediatric heart allocation in Eurotransplant (ET) has evolved over the past decades to better serve patients and improve utilization. Pediatric heart transplants (HT) account for 6% of the annual transplant volume in ET. Death rates on the pediatric heart transplant waiting list have decreased over the years, from 25% in 1997 to 18% in 2011. Within the first year after listing, 32% of all infants (<12 months), 20% of all children aged 1–10 years, and 15% of all children aged 11–15 years died without having received a heart transplant. Survival after transplantation improved over the years, and in almost a decade, the 1‐year survival went from 83% to 89%, and the 3‐year rates increased from 81% to 85%. Improved medical management of heart failure patients and the availability of mechanical support for children have significantly improved the prospects for children on the heart transplant waiting list.